2015
DOI: 10.1111/gfs.12161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tree cover on the biomass and diversity of the herbaceous layer in a Mediterranean dehesa

Abstract: Mediterranean dehesas are an archetypal example of high nature value farmland in Europe. To better understand the interactions between trees and grasslands in the conservation and management of the dehesa, we measured, over 3 years, the contribution of scattered trees to the diversity and biomass dry-matter (DM) yield of the herb layer and the relationship between the herb layer (biomass and diversity interaction) and the trees. The study was based on 135 subplots representing four aspects and three distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…This was driven by a high root biomass, peaking at around 8000 kg ha −1 despite being calculated based on only the top 13 cm. Other studies in similar landscapes in southwestern Europe found maximum root masses of around 2000 kg ha −1 (dependent on cover type; Rolo and Moreno, 2012), 2500 kg ha −1 (Jongen et al, 2013) or under 300-400 kg ha −1 in nearby walnut forestry (López-Díaz et al, 2017), where pasture production was around 2 times higher than our site (Gerardo Moreno, personal communication, 2018). Despite sampling soil profiles to deeper depths, root : shoot ratios at these sites were considerably lower than ours (e.g.…”
Section: Changes In Root : Shoot Ratiosupporting
confidence: 44%
See 2 more Smart Citations
“…This was driven by a high root biomass, peaking at around 8000 kg ha −1 despite being calculated based on only the top 13 cm. Other studies in similar landscapes in southwestern Europe found maximum root masses of around 2000 kg ha −1 (dependent on cover type; Rolo and Moreno, 2012), 2500 kg ha −1 (Jongen et al, 2013) or under 300-400 kg ha −1 in nearby walnut forestry (López-Díaz et al, 2017), where pasture production was around 2 times higher than our site (Gerardo Moreno, personal communication, 2018). Despite sampling soil profiles to deeper depths, root : shoot ratios at these sites were considerably lower than ours (e.g.…”
Section: Changes In Root : Shoot Ratiosupporting
confidence: 44%
“…The same difference in roots between habitat type was not found from minirhizotrons, where we consistently observed greater RLD in open pasture throughout the year. Between tree-covered and pasture areas of dehesas there are major differences in herbaceous layer diversity (López-Carrasco et al, 2015) and community vegetation composition (Marañon, 1986), which affects plant trait distributions. RLD and specific root length are important below-ground plant traits linked to plants' ability to explore soil and acquire Normalized difference vegetation index (NDVI) and grassland green chromatic coordinate (GCC).…”
Section: Treatment and Microhabitat Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…() have suggested that an option for sustainable livestock production is the adoption of silvopastoral system (SPS). Among the productive and environmental benefits of the SPS, the following stand out: Improved soil nutrient availability, increased animal production associated with thermal comfort, and higher crude protein (CP) content of forage, as well as the possibility of income diversification in the property (Baliscei et al., ; Kyriazopoulos, Abraham, Parissi, Koukoura, & Nastis, ; Murgueitio, Calle, Uribe, Calle, & Solorio, ; Paciullo et al., ), and environmental services, such as increased biodiversity, sequestration of atmospheric carbon and mitigation of greenhouse gases (Alves, Madari, & Boddey, ; López‐Carrasco, López‐Sánchez, San Miguel, & Roig, ).…”
Section: Introductionmentioning
confidence: 99%
“…Forest grasslands can be, therefore, important foraging habitats for Turtle Doves. Differently to farmland areas, where weed seeds are directly limited by agricultural practices, factors as scattered tree presence, grazing and annual rainfall are the main drivers of herbaceous community characteristics in forest areas , López-Carrasco et al 2015, López-Sánchez et al 2016. The abundance of weed species whose seeds are consumed by Turtle Dove in this type of habitats vary depending on grazing management (Tarrega et al 2009, López-Sánchez et al 2016.…”
Section: Introductionmentioning
confidence: 99%